A 13-LOX participates in the biosynthesis of JAs and is related to the accumulation of baicalein and wogonin in Scutellaria baicalensis - Geng, Dali; Wang, Rongyu; Zhang, Ya; Lu, Heng; Dong, Hongjing; Liu, Wei; Guo, Lanping; Wang, Xiao (Frontiers in Plant Science, 2023)
Although baicalein and wogonin contents in Scutellaria baicalensis, a traditional Chinese herb, are known to be regulated by jasmonic acid, the exact mechanism by jasmonic acid regulates the accumulation of baicalein and wogonin remains unclear.In this study, we discovered SbLOX3, a gene encoding 13-lipoxygenase from the roots of S. baicalensis, which plays a important role in the biosynthesis of jasmonic acid. The contents of methyl jasmonate, baicalin, wogonin, and three metabolic intermediates of methyl jasmonate, 13-HPOT, OPDA and OPC-8, were downregulated in the hair roots of the SbLOX3 RNAi lines. We confirmed that SbLOX3 was induced by drought stress simulated by PEG and Fusarium oxysporum, which subsequently led to changes in the content of MeJA, baicalin, and wogonin.Taken together, our results indicate that a 13-LOX is involved in the biosynthesis of jasmonic acid, and regulates the accumulation of baicalein and wogonin in S. baicalensis roots.